Improving Digital Design Literacy through Figma-Based UI/UX Training at Qotrun Nada Islamic Boarding School Jakarta Indonesia - Abdul Haris Muchtar; Mariah; Sujoko Winanto; Andi Nur Akifah; Alifa Nur Azizah; Alisha Zaharani; Latifah Fauzia; Marizke Mega Utami (SocietalServe: Journal of Community Engagement and Services, 2026)
This study examines the implementation of a Figma-based UI/UX training program aimed at improving digital design literacy among students at Qotrun Nada Islamic Boarding School, Jakarta. The program was developed to address the limited digital competencies and practical design skills commonly found among santri in traditional Islamic educational environments. Using a project-based learning and mentoring approach, participants were introduced to fundamental concepts of User Interface (UI), User Experience (UX), and collaborative digital design using Figma. The activities included workshops, practical design exercises, mentoring sessions, and prototype development projects. The findings demonstrated significant improvements in students’ digital literacy, communication skills, teamwork, creativity, and confidence in using technology. Students successfully produced simple website prototypes that reflected basic usability and visual design principles. Furthermore, the integration of digital literacy training within the pesantren environment showed that technological skill development can be harmonized with Islamic educational values and community empowerment initiatives